1995
DOI: 10.1111/j.1476-5381.1995.tb16378.x
|View full text |Cite
|
Sign up to set email alerts
|

A role for Q type Ca2+ channels in neurotransmission in the rat urinary bladder

Abstract: 1 In isolated bladder strips of the rat, a substantial component (46%) of the Ca2"-dependent contractile response to electrical field stimulation (5 Hz) was resistant to combined block of both N and P type Ca2`channels by o-conotoxin-GVIA (300 nM) and co-agatoxin-IVA (100 nM) respectively.2 The resistant portion (non-N, non-P) was sensitive to co-conotoxin-MVIIC (3 gM), which in addition to N and P also blocks Q type channels at this concentration. co-Conotoxin-MVIIC administered alone, inhibited the neurogeni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
22
0

Year Published

1996
1996
2014
2014

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(26 citation statements)
references
References 21 publications
4
22
0
Order By: Relevance
“…However, the residual contraction can be abolished by og-contoxin-MVIIC and co-agatoxin-IVA, blockers of P-and Q-type channels [19,20]. Interestingly, this study suggested that the cholinergic component of contraction was largely abolished .by N-type Ca 2+ channel inhibition, whereas the purinergic component was dependent largely on P and Q-type Ca 2+ channels.…”
Section: Ca 2+ Channels In Detrusor Smooth Musclementioning
confidence: 70%
“…However, the residual contraction can be abolished by og-contoxin-MVIIC and co-agatoxin-IVA, blockers of P-and Q-type channels [19,20]. Interestingly, this study suggested that the cholinergic component of contraction was largely abolished .by N-type Ca 2+ channel inhibition, whereas the purinergic component was dependent largely on P and Q-type Ca 2+ channels.…”
Section: Ca 2+ Channels In Detrusor Smooth Musclementioning
confidence: 70%
“…Several studies have shown that N-type VDCCs mediate neurotransmitter release from NANC nerves (Maggi et al 1988;De Luca et al 1990;Hata et al 1992;Boeckxstaens et al 1993). Recently, Q-type VDCCs have also been shown to be involved in the release of neurotransmitters, including nitric oxide in the rabbit urethra (Frew and Lundy 1995;Zygmunt et al 1995). In contrast, L, T and P-type VDCCs are believed to play a minor role in transmitter release from NANC nerves (Hata et al 1992;Boeckxstaens et al 1993;Zygmunt et al 1995;Zagorodnyuk and Maggi 1994).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, transmitter release from parasympathetic neurons in the mouse bladder involves a combination of N-, P-, and Q-type channels. During preparation of this manuscript, evidence for a role of Q-type channels in transmitter release from parasympathetic neurons in the rat bladder has been published (Frew and Lundy, 1995).…”
Section: Calcium Channel Subtypes Mediating the Whole Contractionmentioning
confidence: 99%